Linguistic Landscape of Jalan Gajah Mada Heritage Area in Denpasar City - Ketut Widya Purnawati; Ketut Artawa; Made Sri Satyawati (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
This study aims to explain the contestation of languages on outdoor signboards found in the heritage area of Jalan Gajah Mada in terms of linguistic landscape and how the implementations of government policies for language use in the public space. The heritage area of Jalan Gajah Mada was originally a trading center but recently it is starting to be developed into a tourist attraction of Denpasar old city The study was done by analysing 275 photos of outdoor signboards which were taken along the Jalan Gajah Mada. Those photos were classified based on the type of outdoor signboards, the maker, the number of languages, the number of scripts. The results show that the language that is mostly used in outdoor signboards in this area is Indonesian, eventhough the shops are mostly owned by Chinese descendants and several Indian and Arabian descendants. The study also showed that an outdoor signboard can have one, two, three, or even four languages simultaneously. For those outdoor signboards that use three and four languages, the two of them for sure are Indonesian and English. In accordance with the Regulation of the Governor of Bali Province Number 80 of 2018, especially with the regulation of the use of Balinese and Roman script, the implementation of government policies has not been implemented consistently. The outdoor signboards of government agency names were written exactly following the rules while other outdoor signboards are not.